Optimalisasi Ruang Kosong Bandara untuk Meningkatkan Pendapatan Non-Aeronautika melalui Layanan dan Bisnis Tambahan - Muchamad Nur Syaifulrahman; Muhammad Tunjung Rohmatullah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the strategy of utilizing vacant spaces within airports to enhance non-aeronautical revenue through collaboration with Micro, Small, and Medium Enterprises (MSMEs). Given the growing importance of non-aeronautical revenue sources in the aviation industry, this research focuses on how airports can optimize underutilized spaces for commercial purposes. The research method applied is library research, where relevant literature, journals, and previous studies are reviewed to gain insights into successful strategies and best practices. The findings of the study indicate that the development of commercial spaces, such as fast-food tenants, retail outlets, and photo booths, can significantly enhance the passenger experience by providing convenient services and entertainment. Additionally, these developments offer a sustainable alternative revenue stream for airports, diversifying income beyond traditional aeronautical activities. The research also explores the role of the Value Proposition Canvas business model to assess the alignment between the value offered by these services and the needs of passengers. By applying this model, the study emphasizes the importance of understanding customer expectations and ensuring that airport services meet these demands. The analysis further highlights that successful implementation of these strategies requires careful planning, including collaboration between airport management, MSMEs, local governments, and sponsors. Building strong partnerships and ensuring mutual benefit are critical for maximizing the non-aeronautical revenue potential. The study concludes by suggesting that airports can leverage vacant spaces more effectively to not only boost revenue but also improve the overall passenger experience, contributing to the long-term sustainability and growth of the airport sector.